La fertilización y el largo del ciclo de uso en la productividad del pasto Faragua (Hyparrhenia rufa (Ness) Stapf) - Pinzón Quezada, Bólivar R. (IICA, San José (Costa Rica), 2014)
Tesis (Mag. Sc.) -- IICA, San José (Costa Rica), 1976